Impact of a qualitative assessment approach for neonatal abstinence syndrome management: experience of a European reference center - Mariana Cortez Ferreira; Ana Moura Figueiredo; Joaquim Pitorra; Joana Mesquita da Silva (BMC, 2024)
Abstract Background The management of infants at risk of neonatal abstinence syndrome (NAS) remains challenging. In 2000 Maternidade Bissaya Barreto implemented a strategy based on the qualitative assessment of neonates and in 2018 the Eat, Sleep, Console (ESC) approach, a tool based on similar concepts, was created. The aim is to assess the efficacy of a qualitative assessment of infants at risk, compare it with the ESC approach and report temporal trends of NAS in a European hospital. Methods Retrospective cohort study of all infants of mothers with a history of drug abuse during pregnancy admitted to a tertiary European centre between January 2010 and December 2021. The therapeutical decision was guided by a qualitative assessment of the newborn's well-being. The ESC approach was retrospectively determined. Pharmacologic treatment was used as a last resort. The clinical outcomes and therapeutic strategies employed were evaluated. Statistical association was evaluated. The incidence rate per 1000 births was calculated and temporal trend differences were identified. Results A total of 79 neonates at risk were included, of whom 40 (50.6%) developed NAS. Consolability was the most affected criterion (35.0%), followed by feeding difficulties (12.5%). Sleep was affected less frequently (5.0%). Overall, 37.5% of infants failed to meet at least one of the criteria. All neonates with a positive ESC failed the qualitative assessment (p = 1.000) After optimization of nonpharmacologic measures, drug therapy was still necessary in four cases (10.0% of infants with the syndrome). The incidence rate of NAS decreased from 3.9 per 1000 births in 2010 to 0.0 per 1000 births in 2021 (p = 0.025). Conclusion The qualitative assessment of the infant based on the ability to feed, sleep and be consoled correctly identified neonates at risk and led to a significant reduction in the use of drug therapy. The incidence rate of NAS decreased during the study period.